Intratumoral talimogene laherparepvec injection with concurrent preoperative radiation in patients with locally advanced soft-tissue sarcoma of the trunk and extremities: phase IB/II trial. Issue 7 (30th July 2021) - Monga, Varun; Miller, Benjamin J; Tanas, Munir; Boukhar, Sarag; Allen, Bryan; Anderson, Carryn; Stephens, Laura; Hartwig, Stacey; Varga, Steven; Houtman, Jon; Wang, Lei; Zhang, Weizhou; et al.
Abstract : Background: Soft-tissue sarcomas (STS) in the extremities and trunk treated with standard-of-care preoperative external beam radiation therapy (EBRT) followed by surgical resection are associated with local and distant relapses. In preclinical studies, oncolytic virotherapy in sarcoma has demonstrated antitumor effects via direct intratumoral oncolysis and cytotoxic T-cell–mediated immune responses. Talimogene laherparepvec (TVEC) is a replication-competent, immune-enhanced, oncolytic herpes simplex virus type 1 engineered for intratumoral injection; it has been approved by the FDA for the treatment of locally advanced and metastatic melanoma. Methods: We explored a novel combination of TVEC with standard-of-care EBRT administered preoperatively in patients with locally advanced STS of the extremities and trunk in a phase IB/II clinical trial. Thirty patients with primary STS >5 cm for which EBRT was indicated to achieve negative margins were enrolled. FDA-approved TVEC doses were used. Immune correlative studies in peripheral blood, biopsy and resected tumor tissues were performed. Results: No dose-limiting toxicity was observed. Adverse events were similar to those reported in prior studies with TVEC. One patient with myxoid liposarcoma exhibited a partial response. Seven of the 29 (24%) evaluable patients achieved 95% pathological necrosis. None of the patients developed a herpes infection due to the treatment. Eight of the 29 (27%) patients developed postoperative wound complications, which is consistent with previous studies. None of the patients developed local recurrence after surgical resection of the primary sarcoma. 2-year progression-free and overall survival were 57% and 88%, respectively. Caspase-3 demonstrated increased expression of both in TVEC-treated tissue samples as compared with control samples treated with radiation alone. Conclusion: Preoperative intratumoral TVEC with concurrent EBRT for locally advanced STS is safe and well-tolerated. This combination treatment may enhance immune responses in some cases but did not increase the proposed rate of pathological necrosis. The Caspase-3 biomarker may be associated with a positive effect of TVEC in sarcoma tumor tissue and should be explored in future studies. Trial registration number: NCT02453191 .